(untitled) (KYAMC Journal, 2018)
Vomiting and aspiration usually occurs in those patients who are to be operated under general anesthesia in full stomach. It may occur in empty stomach also. It is an extreme emergency and needs urgent management. When it occurs, it worries an anesthetist as well as surgeon also. Immediate management should be started. As early as possible the patient should be turned in to lateral side with trendelenburg position. The pharynx and esophagus should be sucked as quickly as possible. All the resuscitator equipments should be ready at hand. Preoperative assessment and clinical examination is very important. Particularly history must be taken whether the patient had taken any food or not for the last six hours. Treatment should be adequate and prompt to avoid any disaster. If necessary the patient should be shifted to ICU for quick recovery. Here we present a case of 22 years old young man who developed vomiting and aspiration during tonsillectomy operation in North Bengal Medical College on 30th may, 2015. KYAMC Journal Vol. 8, No.-2, Jan 2018, Page 36-39